Design of Deformation Monitoring System for Volcano Mitigation. (August 2016) - Islamy, M R F; Salam, R A; Munir, M M; Irsyam, M; Khairurrijal,
Abstract: Indonesia has many active volcanoes that are potentially disastrous. It needs good mitigation systems to prevent victims and to reduce casualties from potential disaster caused by volcanoes eruption. Therefore, the system to monitor the deformation of volcano was built. This system employed telemetry with the combination of Radio Frequency (RF) communications of XBEE and General Packet Radio Service (GPRS) communication of SIM900. There are two types of modules in this system, first is the coordinator as a parent and second is the node as a child. Each node was connected to coordinator forming a Wireless Sensor Network (WSN) with a star topology and it has an inclinometer based sensor, a Global Positioning System (GPS), and an XBEE module. The coordinator collects data to each node, one a time, to prevent collision data between nodes, save data to SD Card and transmit data to web server via GPRS. Inclinometer was calibrated with self-built in calibrator and tested in high temperature environment to check the durability. The GPS was tested by displaying its position in web server via Google Map Application Protocol Interface (API v.3). It was shown that the coordinator can receive and transmit data from every node to web server very well and the system works well in a high temperature environment.